Workforce Characteristics, Workplace and Job Satisfaction, Stress, Burnout, and Happiness of Music Therapists in the United States - Meadows, Anthony; Eyre, Lillian; Gollenberg, Audra (Voices: A World Forum for Music Therapy, 2022)
This survey research examined the work lives of music therapists in the United States. With the inclusion of data on salary, workplace and job satisfaction, stress, burnout, and happiness, a comprehensive picture of the working lives of music therapists emerges. On the whole, music therapists appear to be generally happy with their workplace and job conditions and to experience moderate stress and low burnout. Data regarding salaries reveal a complex economic landscape. Although the average full-time salary of a music therapist was 51,099.69, salaries varied widely, with newly credentialed music therapists and those with less than six years of experience reporting lower average salaries. Variations in salaries, stress, burnout, and happiness were also evident across workplaces. Implications for the profession, including advocacy efforts, support for early-career professionals, and additional support for career development, invite further discussion.